Tracheotomy in the SARS‐CoV‐2 pandemic. Issue 7 (29th April 2020) - Skoog, Hunter; Withrow, Kirk; Jeyarajan, Harishanker; Greene, Benjamin; Batra, Hitesh; Cox, Daniel; Pierce, Albert; Grayson, Jessica W.; Carroll, William R.
Abstract: The severe acute respiratory syndrome (SARS)‐CoV‐2 pandemic continues to produce a large number of patients with chronic respiratory failure and ventilator dependence. As such, surgeons will be called upon to perform tracheotomy for a subset of these chronically intubated patients. As seen during the SARS and the SARS‐CoV‐2 outbreaks, aerosol‐generating procedures (AGP) have been associated with higher rates of infection of medical personnel and potential acceleration of viral dissemination throughout the medical center. Therefore, a thoughtful approach to tracheotomy (and other AGPs) is imperative and maintaining traditional management norms may be unsuitable or even potentially harmful. We sought to review the existing evidence informing best practices and then develop straightforward guidelines for tracheotomy during the SARS‐CoV‐2 pandemic. This communication is the product of those efforts and is based on national and international experience with the current SARS‐CoV‐2 pandemic and the SARS epidemic of 2002/2003.